The efficiency cost of protective measures in climate policy. (May 2017) - Böhringer, Christoph; Garcia-Muros, Xaquin; Cazcarro, Ignacio; Arto, Iñaki
Abstract: Despite recent achievements towards a global climate agreement, climate action to reduce greenhouse gas emissions remains quite heterogeneous across countries. Energy-intensive and trade-exposed (EITE) industries in industrialized countries are concerned on stringent domestic emission pricing that puts them at a competitive disadvantage against producers of similar goods in other countries with more lenient emission regulation. This paper focuses on climate policy design in the United States of America (US) and compares the economic implications of four alternative protective measures for US EITE industries: (i) output-based rebates, (ii) exemptions from emission pricing, (iii) energy intensity standards, and (iv) carbon intensity standards. Using a large-scale computable general equilibrium model we quantify how these protective measures affect competitiveness of US EITE industries. We find that protective measures can improve common trade-related competitiveness indicators such as revealed comparative advantage or relative world trade shares but at the same time may lead to a decline in the output value for EITE industries because of negative income effects. The economy-wide cost of emission abatement under protective measures increase as compared to uniform emission pricing stand-alone such that the gains of protective measures for EITE exports may be more than compensated through losses in domestic EITE demand. Highlights: We assess impacts for US emission-intensive and trade-exposed (EITE) industries. EITE impacts are quantified via competitiveness metrics and production output. Protective measures reduce adverse competitiveness impacts but can depress output. Output losses are due to negative income effects that reduce domestic EITE demand. Protective measures run the risk of making US climate policy much more costly.